Effect of Shrinking and Swelling of Wood on Solid Wood Table - Tankut, Nurgül; Tankut, Ali Naci (Bartın Üniversitesi, 2001)
[Abstract Not Available]
Odunun Daralma ve Genişlemesinin Masif Masa Üzerine Etkisi